Understanding past climates: modelling ancient weather (ISO image of CD-ROM) - Valdes, P J; Spicer, R A; Sellwood, B W; Palmer, D C (Gordon and Breach Science Publishers, 1999)
This CD contains results from some of the most sophisticated computer climate model experiments. Technial information on the model parameter are supplied, but so too is a wealth of illustrated and animated background information that will be useful to those not familiar with climate modelling or the interpretation of paleoclimates from the geological record. Climate model results for the Late Carboniferous, latest Jurassic, middle and latest Cretaceous, Eocene, Miocene, glacial inception (1250000 yrs), the last glacial maximum (21000 yrs), mid Holocene (12000 yrs), the present day and the present day with 2x present levels of atmospheric carbon dioxide are given together with data of the oberserved present day climate. Results are given in the form of animations for temperature, soil moisture, precipitation, mean sea level air pressure, snow depth, storminess and cloudiness. The operation of the models is explained along with information on the structure and dynamics of the atmosphere and how the geological record can be used to determine past climate.